Near infrared light-mediated photoactivation of cytotoxic Re(i) complexes by using lanthanide-doped upconversion nanoparticles. Issue 36 (31st August 2016) - Hu, Ming; Zhao, Jixian; Ai, Xiangzhao; Budanovic, Maja; Mu, Jing; Webster, Richard D.; Cao, Qian; Mao, Zongwan; Xing, Bengang
Abstract : Photoactivation of cytotoxic Re(i ) complexes by using lanthanide doped upconversion nanoparticles upon near infrared illumination was demonstrated to selectively activate Re(i ) complexes in tumor cells for enhanced anti-cancer effect. Abstract : Platinum-based chemotherapy, although it has been well proven to be effective in the battle against cancer, suffers from limited specificity, severe side effects and drug resistance. The development of new alternatives with potent anticancer effects and improved specificity is therefore urgently needed. Recently, there are some new chemotherapy reagents based on photoactive Re(i ) complexes which have been reported as promising alternatives to improve specificity mainly attributed to the spatial and temporal activation process by light irradiation. However, most of them respond to short-wavelength light ( e.g. UV, blue or green light), which may cause unwanted photo damage to cells. Herein, we demonstrate a system for near-infrared (NIR) light controlled activation of Re(i ) complex cytotoxicity by integration of photoactivatable Re(i ) complexes and lanthanide-doped upconversion nanoparticles (UCNPs). Upon NIR irradiation at 980 nm, the Re(i ) complex can be locally activated by upconverted UV light emitted from UCNPs and subsequently leads to enhanced cell lethality. Cytotoxicity studies showed effective inactivation of both drug susceptible human ovarian carcinoma A2780 cells and cisplatin resistant subline A2780cis cells by our UCNP based system with NIR irradiation, and there was minimum light toxicity observed in the whole process, suggesting that such a system could provide a promising strategy to control localized activation of Re(i ) complexes and therefore minimize potential side effects.